Подвижницька праця культурно-освітнього діяча і збирача українського фольклору - Козар, Л. (Народна творчість та етнографія, 2005)
This article is devoted to the work of the collector of Ukrainian folklore of the end of the 19th beginning of the 20th Century – Vasyl Stepanenko, who was at the same time an active in public work. He collected more then 400-folklore texts, which were published in Hrynchenko's materials. His public work is well knowing because he was a head of the public publishing company in Kyiv from 1899 to 1919. Many famous Ukrainian folklorists and public figures mentioned his hard work and talents at the time.